Various secondary metabolites of endophytic fungi induced by a newly modified medium and their insecticidal activities - JELLY MILINIA PUSPITA SARI; SITI HERLINDA; ELFITA ELFITA; SUWANDI SUWANDI (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Sari JMP, Herlinda S, Elfita, Suwandi S. 2025. Various secondary metabolites of endophytic fungi induced by a newly modified medium and their insecticidal activities. Biodiversitas 26: 1881-1890. This research aimed to identify and increase the variation of secondary metabolites of Penicillium citrinum, Beauveria bassiana, and Metarhizium anisopliae from South Sumatra and to determine their insecticidal activities. The fungi were grown on a Glucose Yeast Extract Broth (GYB) medium enriched with cricket powder and a Potato Dextrose Broth (PDB) medium. Secondary metabolite compounds from peaks in the LC-MS chromatograms of the crude extract of P. citrinum cultured in GYB medium were guanidine acetate, 8-deoxygartanin, abafungin, and 2-amino-5-carboethoxy-4-hydroxypyrimidine. Isoquinoline and leucic acid were detected in P. citrinum extracts of PDB culture. B. bassiana could produce psoralidin and L-(+)-lysine from GYB culture and adenine, guanidine acetate, ethyl carbazate, aceglutamide, and L-(+)-lysine from PDB culture. M. anisopliae could synthesize cytosine, adenine, n-aminoguanidine, azanidazole, phenol, methyl carbazate, and antiarol from GYB medium and 3-(Dimethylamino)-1-propanethiol and 2-(7H-Pyrrolo[2,3-d] pyrimidin-4-yl)-1H-isoindole-1,3(2H)-dione from PDB medium. P. citrinum extract from GYB culture caused the highest larval mortality (98%) of Spodoptera frugiperda. Nevertheless, the mortality was not significantly different from that induced by B. bassiana (96.67%) and M. anisopliae (97.33%) from GYB culture. Thus, the fungi cultured in the GYB medium have the potential to synthesize more secondary metabolite compounds, and they have high insecticidal activities, inducing high larval mortality.